CONCEPTUAL BASICS OF STANDARDIZATION OF ECOLOGICAL AND FREE FLOW FOR RIVERS IN KAZAKHSTAN - Malik Z. Burlibayev; D.M. Burlibayeva (Водное хозяйство России: проблемы, технологии, управление)
The article presents methodical proposals concerning replacement of the approved norms for calculation of sanitary releases from reservoirs for ecological flow, proposals for the methods of determination of the ecological flow parameters that could be accepted for Kazakhstan for the river flow regulating. We tried to use the developed methodical principles based on ecological safety for determination of scientifically proved quantitative dependencies and norms of the flow permissible withdrawal for the main rivers of Kazakhstan. Within the framework of the performed studies Kazakhstan as the Chairperson of the Convention on Transboundary Water Courses and Water Bodies of the UN EEC intends to present the methods for determination of ecological flow and permissible river flow withdrawal for discussion.